Critical Analysis of the book “Lessons of Arabic Rhetoric toward a New Idea” by Al- Azhar Al-zzennad - nadiya dadpour; Mohammad Khaqani Isfahani (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Critical analysis increases the efficiency of considered text in different aspects. They reveal positive and negative features of the text. Rhetoric books are no exception from this evaluation. Evaluating rhetoric books is important due to two points: Enhancing/Improving quality of educational rhetoric books and finding modern rhetoric viewpoints and comparing them with other rhetoric results. The purpose of this article is to evaluate lessons of Arabic rhetoric toward a new idea from two perspectives: Efficiency level in rhetoric as well academic education. The method of analysis is analytic and descriptive. The paper aims to analyze the positive and negative aspects of the book by first reporting the context of the book. In addition, it aims to show AlAzhar’s book view for academic tuition all over the world. The results of this research show the book "Lessons of Arabic Rhetoric toward a New Idea", has compounded classic rhetoric with modern masterful rhetoric discovery. However, the frame of the book turns around classic rhetoric. This book can be taught in basic levels (BA) as a main source and in high levels (MA) as a derivative source. Although the writer has done his best, he has not paid attention to some classic rhetoric discussions.